Endocrine disrupting chemicals and obesity prevention: scoping review - Mojca Amon; Tina Kek; Irma Virant Klun (BMC, 2024)
Abstract Introduction Exposure to endocrine disrupting chemicals (EDCs) can result in alterations of natural hormones in the body. The aim of this review article is to highlight the knowledge about EDCs and obesity. Methods A scoping review of the electronic literature was performed using PubMed platform for studies on EDCs and obesity published between the years 2013-2023. A total of 10 systematic reviews and meta-analysis studies met our inclusion criteria on more prominent EDCs focusing mainly on bisphenols, including parabens, triclosan, and phthalates, and their association with obesity. Design Scoping review. Results EDCs, mostly bisphenols and phthalates, are related to health effects, while there is less information on the impact of parabens and triclosan. A series of negative physiological effects involving obesogenic, diabetogenic, carcinogenic, and inflammatory mechanisms as well as epigenetic and microbiota modulations was related to a prolonged EDCs exposure. A more profound research of particular pollutants is required to illuminate the accelerating effects of particular EDCs, mixtures or their metabolites on the mechanism of the development of obesity. Conclusion Considering the characteristics of EDCs and the heterogeneity of studies, it is necessary to design specific studies of effect tracking and, in particular, education about daily preventive exposure to EDCs for the preservation of long-term public health.